Armenians in Old Poland and Austrian Galicia: A Demographic and Historical Study - Wasyl, Franciszek (Księgarnia Akademicka Publishing, 2021)
This monograph, which complements the existing body of work on the Armenian diaspora in a Central European context, is the first demographic synthesis devoted to the Armenian community in Old Poland and Austrian Galicia (1772–1860). It is the story of the biological and cultural trajectory of a human life: birth, marriage, childbearing, family life, sickness, old age and death. The author enumerates the Armenian diaspora in Austrian Galicia and poses questions regarding Armenian identity, religious practices and community life. The book includes a discussion of archival sources and contains a selection of the parish family registers (status animarum) in the annex. These documents, which not only enhance the narration but also detail the Armenian families, can stimulate further research and support genealogical investigations. Publication co-published with Brill Ferdinand Schöningh.